Skills, knowledge and expertise in sport - Breivik, Gunnar (Routledge, Taylor & Francis Group, 2018)
Taking part in a sport means that one must acquire the relevant skills: mental, physical and strategic. This book presents a new perspective on the role of skills, knowledge and intentionality in sporting contexts, examining how these skills and practical 'know how' can be perfected to a level of expertise.